Motor pump revolution in Ethiopia: promises at a crossroads - Dessalegn, Mengistu; Merrey, Douglas J. (2015)
In sub-Saharan Africa, motor pump irrigation is at an earlier stage than in Asia but is growing rapidly in many countries. The focus of both policy and research in Africa to date has been on facilitating supply chains to make pumps available at a reasonable price. In Africa, pump irrigation is mainly based on two sources: shallow groundwater aquifers and small streams and rivers. Both usually have limited and variable yields. We present a case study from Ethiopia where pump irrigation based on small rivers and streams is expanding rapidly, and draw parallels to experiences in Asia and other African countries. We show that while farmers understand the social nature of community-managed irrigation, they share with policymakers a narrow understanding of pump irrigation as being primarily 'technical'. They perceive pumps as liberating them from the 'social' limitations of traditional communal irrigation. However, the rapid expansion of pump irrigation is leading to increasing competition and conflict over the limited water resource. We analyse the wider implications for Africa of this blindness to the social dimension of pump irrigation and offer suggestions on future policy and applied research to address the problem before it becomes a widespread crisis.